Left Ventricular Pseudoaneurysms in Children—A Case Series. Issue 4 (July 2020) - Sreevathsa, Prasad; Ram, Duvuru; Munuswamy, Hemachandren; Satyavathi, Davulury Sri; Sai Chandran, Bathal Vedagiri
Left ventricular pseudoaneurysms are very rare in children. In children, left ventricular pseudoaneurysms can occur following infection, trauma, ischemia, or cardiac surgery. The authors report a series of three cases treated at our hospital with two of the cases having a history of extrapulmonary tuberculosis and one patient with a history of varicella zoster infection.